Closure of abdominal wall by means of polyethylene tubes - Praderi, Raúl; Bogliaccini, Gustavo; Navarro, Teodoro (Cirugía del Uruguay, 1981)
the paper describes a quick and simple procedure for closure of the abdominal wall.